PERINTAH PEJABAT TATA USAHA NEGARA MELALUI TELEPON DAN AKIBAT HUKUMNYA - Muchamad Arif Agung Nugroho (Fakultas Hukum Universitas Wahid Hasyim, 2012)
Orders over the phone about a moratorium on corruption by Wamenkumham remission is an interesting thing to be appointed to the writing of the law, because such events have been detrimental to the interests of the convicted of corruption. Countries such as not having the means to resolve the dispute. Therefore, this paper is to review the legal argumerntasi against the order along with its legal effect. When viewed from the state administrative law and procedural law state administrative courts, then the command can be equated with legal decisions, so it could be the subject of dispute that can be sued in state administrative courts. In addition, the command also meet the criteria for maladministration to be reported to the Ombudsman of the Republic of Indonesia and the recommendations issued by the issuing sanctions against the officials.Key words: administrative official orders, due to legal, ombudsman